Hubungan Asupan Black Garlic Terhadap Gambaran Histopatologi Ginjal Tikus Putih (Rattus Norvegicus) Galur Sprague-Dawley Yang Diinduksi Minyak Jelantah - Dimas Dimas; Putu Ristyaning Ayu Sangging (Medula, 2026)
Cooking oil consumed orally contains toxic substances that can cause cell damage in the kidneys. Black garlic contains antioxidants that can have an anti-toxic effect on the kidneys. This study is a true experimental study using a posttest only control group design to determine whether there is a relationship between black garlic intake and renal histopathology in Sprague-Dawley strain white rats (Rattus norvegicus) induced by used cooking oil. In this study, there were 25 rat samples divided into 5 groups: a control group with distilled water (K1), a control group with waste oil (K2), a 200mg/kgBW group (P1), a 400mg/kgBW group (P2), and an 800mg/kgBW group from the black garlic dose (P3). Microscopic aspects such as cellular infiltration, edema, and necrosis were assessed to evaluate the histopathology of the kidney. The data obtained were then statistically tested using One-Way ANOVA and PostHoc LSD tests. Based on the results of the One-Way ANOVA statistical test, a p-value of 0.000 was obtained, and group P3 had the lowest renal histopathological damage compared to groups P1 and P2. There was a relationship between black garlic intake and the histopathology of the kidneys of Sprague-Dawley strain white rats (Rattus norvegicus) induced by waste oil, and the group with a black garlic dose of 800 mg/kgBW had the lowest histopathological damage to the kidneys compared to the other treatment groups.